2018
DOI: 10.1002/acr.23480
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Lupus Nephritis in the Systemic Lupus International Collaborating Clinics Inception Cohort Using a Multistate Model Approach

Abstract: Patients with estimated GFR <30 ml/minute incurred 10-year costs 15-fold higher than those with normal estimated GFR. By estimating the expected duration in each renal state and incorporating associated annual costs, disease severity at presentation can be used to anticipate future health care costs. This is critical knowledge for cost-effectiveness evaluations of novel therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…About point of services, the inpatient ones were the most expensive in our study, in agreement with other authors who reported both hospitalizations and readmissions as sources of high direct costs. 16 In addition, as the complication advances, the 10-year cumulative costs magnify to approximately 23-fold, 9 which implies that an increase in costs is sometimes predictable and they might increase even before the diagnosis is made. 3 Therefore, the worsening of disease, although difficult, might be preventable or delayed if optimal patient follow-up and attention are achieved.…”
Section: Discussionmentioning
confidence: 99%
“…About point of services, the inpatient ones were the most expensive in our study, in agreement with other authors who reported both hospitalizations and readmissions as sources of high direct costs. 16 In addition, as the complication advances, the 10-year cumulative costs magnify to approximately 23-fold, 9 which implies that an increase in costs is sometimes predictable and they might increase even before the diagnosis is made. 3 Therefore, the worsening of disease, although difficult, might be preventable or delayed if optimal patient follow-up and attention are achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In the US study by Li et al [38], median annual medical costs for patients with SLE and ESKD increased by twofold between Year 1 and Year 5 (US$33,827-66,490), whereas ESKD was also found to be a significant independent contributor to treatment costs (p \ 0.001). In addition, Barber et al [27] reported that predicted mean annual costs related to ESKD were more than 17-fold higher than health states reflecting good renal function.…”
Section: Direct Costsmentioning
confidence: 99%
“…In previous research involving the SLICC inception cohort, we have used similar multistate modeling to estimate long-term direct costs associated with lupus nephritis. We demonstrated that those with lupus nephritis and an estimated glomerular filtration rate (GFR) <30 ml/minute incurred 10-year costs >15-fold than for patients without lupus nephritis and an estimated GFR >60 ml/minute (29). Other researchers have also reported an association between renal damage and direct costs, with one study of 715 patients showing that each unit increase in renal damage was associated with a 24% increase in 4-year direct costs, while there was no association between renal damage and indirect costs (i.e., those due to lost productivity) (30).…”
Section: Discussionmentioning
confidence: 99%